Clinical profiles, electrolytes status in acute strokes and their outcome - Pradhan, Butungeshwar; Majhi, Chakradhar; Panigrahi, Sunil K. (International Journal of Advances in Medicine, 2018)
Background: Intracerebral hemorrhage (ICH) and Ischemic strokes (ISCHS) can occurs along with many metabolic abnormalities in acute stage. Electrolyte disturbances can occurs in acute stage of strokes due to many causes. The aim of the present study is to observe the clinical profiles, electrolytes status in acute stage of strokes and their outcome. Methods: One hundred stroke patients diagnosed clinically and confirmed by CT or MRI within 24 hours of onset were consecutively selected for the study after fulfillment of inclusion criteria in the indoor department of medicine, VSSIMSAR, Burla, Odisha (India), from Nov 2015 to Nov 2017. Baseline Glasgow Coma Scale (GCS), serum electrolytes were estimated along with other biochemical tests as needed. Glasgow Outcome Scale (GOS) was determined after 5th day of strokes. Data were collected and analyzed. Results: Hyponatraemia present in 13 (36.11%) of ICH and 6 (2.38%) ISCHS. Hypokalaemia was present in 7 (9.44%) of ICH and 11(17.19%) ISCHS. Hypocalcaemia was present in 3 (8.33%) of ICH and 18(28.12%) ISCHS. (P 0.0001). Hypomagnesaemia in 2(5.56%) ICH and 21 (32.81%) ISCHS. (P 0.0001). Minor GCS in 38 (62.29%), moderate 15 (24.59%) and severe 8(13.12%) patients with dyselectrolytemia versus 31 (79.48%), 5 (12.82%) and 3 (7.7%) with normal electrolytes respectively. GOS was good in 30 (49.18%), poor 18 (29.51%) and GOS 1 (Deaths) 13 (21.31%) versus 32(82.05%), 5(12.82%) and 1(1.3%) in patients with normal electrolytes status. (P 0.03). Conclusions: E Hyponatraemia and hypoklaemia was very often present in ICH and hypocalcaemia and hypomagnesaemia in ISCHS, Higher rates of morbidity and mortalities was associated with dyselectrolytemia.